Longitudinal Serological Analysis and Neutralizing Antibody Levels in Coronavirus Disease 2019 Convalescent Patients. (3rd November 2020) - Muecksch, Frauke; Wise, Helen; Batchelor, Becky; Squires, Maria; Semple, Elizabeth; Richardson, Claire; McGuire, Jacqueline; Clearly, Sarah; Furrie, Elizabeth; Greig, Neil; Hay, Gordon; Templeton, Kate; et al.
Abstract: Background: Understanding the longitudinal trajectory of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies is crucial for diagnosis of prior infection and predicting future immunity. Methods: We conducted a longitudinal analysis of coronavirus disease 2019 convalescent patients, with neutralizing antibody assays and SARS-CoV-2 serological assay platforms using SARS-CoV-2 spike (S) or nucleocapsid (N) antigens. Results: Sensitivities of serological assays in diagnosing prior SARS-CoV-2 infection changed with time. One widely used commercial platform that had an initial sensitivity of >95% declined to 71% at 81–100 days after diagnosis. The trajectories of median binding antibody titers measured over approximately 3–4 months were not dependent on the use of SARS-CoV-2 N or S proteins as antigen. The median neutralization titer decreased by approximately 45% per month. Each serological assay gave quantitative antibody titers that were correlated with SARS-CoV-2 neutralization titers, but S-based serological assay measurements better predicted neutralization potency. Correlation between S-binding and neutralization titers deteriorated with time, and decreases in neutralization titers were not predicted by changes in S-binding antibody titers. Conclusions: Different SARS-CoV-2 serological assays are more or less well suited for surveillance versus prediction of serum neutralization potency. Extended follow-up should facilitate the establishment of appropriate serological correlates of protection against SARS-CoV-2 reinfection. Abstract : Analysis of coronavirus disease 2019 convalescent patients reveals that neutralizing antibody levels decline rapidly early after infection. Some clinical serological assay platforms give quantitative outputs that predict neutralizing antibody titer, but in some diagnostic sensitivity deteriorates with time after infection.